NFT-based Asset Management System - ÜLKÜ, EYÜP EMRE (My University, 2022)
There are billions of houses, businesses, and lands in the world, and we can prove the ownership of these assets with title deeds prepared by government offices. In the purchase and sale transactions of these titled assets, it is necessary to go through long and complex possess, and the actions that need to be taken do not end here. The asset must also be insured and paid regularly for insurance, tax, and some subscriptions like electricity, water, natural gas, etc. This study aims to create a blockchain-based asset management system that uses NFTs (non-fungible tokens), smart contracts, and the Ethereum network.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; İnşaat Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Civil Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; ENERJİ VE YAKITLAR; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; ENERGY & FUELS; INFORMATION SCIENCE & LIBRARY SCIENCE; ENGINEERING, CIVIL; Yapay Zeka; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Bilgisayar Bilimi Uygulamaları; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; İnşaat ve Yapı Mühendisliği; Kontrol ve Optimizasyon; Artificial Intelligence; Physical Sciences; Computer Networks and Communications; Computer Science Applications; Information Systems and Management; Social Sciences & Humanities; Renewable Energy, Sustainability and the Environment; Civil and Structural Engineering; Control and Optimization; blockchain; NFT; security; smart contract; blockchain; security; NFT; smart contract